Asuhan Keperawatan Pada Pasien Congestive Heart Failure (CHF) Di Ruang Mawar I RSUD dr. Soeselo Kabupaten Tegal - M. Ardes Dwi Saputra; Titis Wening Setyoharsih (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Congestive Heart Failure (CHF) is a condition in which the heart is unable to pump blood effectively due to structural or functional disorders, commonly manifesting as dyspnea, fluid retention, and peripheral edema. Globally, cardiovascular disease is the leading cause of death, with CHF affecting more than 55-65 million people worldwide. Objective: To perform comprehensive nursing care on patient Ny. A with cardiovascular system disorder: Congestive Heart Failure (CHF) in the Mawar I Ward of RSUD dr. Soeselo, Tegal Regency. Methods: This study used a descriptive method through a case study approach. Data were collected via interview, observation, and physical examination. Results: Four nursing diagnoses were identified: ineffective breathing pattern, hypervolemia, activity intolerance, and knowledge deficit. Interventions included respiratory monitoring, hypervolemia management, energy management, and health education on disease process. After two days of nursing implementation, three diagnoses were resolved and one (hypervolemia) was partially resolved. Conclusion: Nursing care for Ny. A with CHF was carried out through assessment, nursing diagnosis, intervention, implementation, and evaluation. Continued interventions are recommended, including fluid balance monitoring, diuretic collaboration, and edema and ascites monitoring.